Education, Self-Efficacy, and Technology Literacy in Encouraging Digital Entrepreneurial Intentions: A Literature Review - Kencana, Aditya Putra; Tan, Gloria; Yabes, Hendy Aprilian; Nabila Irsa Anggraini (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2025)
The development of digital technology has prompted the emergence of a new form of digital platform-based entrepreneurship, known as digital entrepreneurship. This study aims to systematically examine the latest scientific findings regarding the factors that affect digital entrepreneurial intention in the period 2021 to 2025. The method used was a literature review of 20 articles published in reputable international journals and obtained through the ScienceDirect database. The analysis was carried out in a qualitative descriptive manner with a narrative approach and thematic synthesis. The results of the study show that the main factors that influence digital entrepreneurship intentions include digital self-efficacy, attitudes towards technology, entrepreneurship education, fintech literacy, and social support. The dominant theoretical approaches used in explaining this phenomenon include the Theory of Planned Behavior (TPB), Social Cognitive Career Theory (SCCT), and Stimulus-Organism-Response (SOR). These findings have theoretical implications in enriching the model of the formation of entrepreneurial intentions in the digital era, as well as practical implications in designing education, training, and policy programs that support the development of digital entrepreneurship competencies, especially for the younger generation and students.